Effect of Maternal Factors and Fetomaternal Glucose Homeostasis on Birth Weight and Postnatal Growth - (:unkn) unknown (My University, 2015)
0

Objective: It is important to identify the possible risk factors for the occurrence of large for gestational age (LGA) in newborns and to determine the effect of birth weight and metabolic parameters on subsequent growth. We aimed to determine the effects of maternal weight, weight gain during pregnancy, maternal hemoglobin A1c (HbA1c), C-peptide and insulin as well as cord C-peptide and insulin levels on birth weight and postnatal growth during the first two years of life. Methods: Healthy, non-diabetic mothers and term singleton newborns were included in this prospective case-control cohort study. Fasting maternal glucose, HbA1c, C-peptide and insulin levels were studied. Cord blood was analyzed for C-peptide and insulin. At birth, newborns were divided into two groups according to birth size: LGA and appropriate for GA (AGA). Infants were followed at six-month intervals for two years and their length and weight were recorded. Results: Forty LGA and 43 AGA infants were included in the study. Birth weight standard deviation score (SDS) was positively correlated with maternal body mass index (BMI) before delivery (r=0.2, p=0.04) and with weight gain during pregnancy (r=0.2, p=0.04). In multivariate analyses, the strongest association with macrosomia was a maternal C-peptide level >3.85 ng/mL (OR=20). Although the LGA group showed decreased growth by the 6-month of follow-up, the differences between the LGA and AGA groups in weight and length SDS persisted over the 2 years of follow-up.Conclusion: The control of maternal BMI and prevention of overt weight gain during pregnancy may prevent excessive birth weight. The effect of the in utero metabolic environment on the weight and length SDS of infants born LGA persists until at least two years of age.
Keywords: Endokrinoloji ve Metabolizma; Pediatri